The perception of Acehnese parents on heritage language maintenance: A quantitative approach - Ida Muliawati; Dara Yusnida (Studies in English Language and Education, 2022)
Family is the ideal platform to maintain the indigenous language, and parents are the core feature in promoting it to the children. Many previous studies have concentrated on the Acehnese younger generations’ declination use of Acehnese. Their perception of the language is initially linked to the parents’ attitude towards it since the parents’ attitude determines the children’s perception of it. Hence, the present research aims to fill in the gap by assessing the language attitude of the Acehnese parents living in the urban areas on Acehnese and searching for their efforts in passing the language to their descendants. Fifty-five respondents from three different districts in Banda Aceh were purposely selected by considering some criteria to fulfill the need of this research. The data were collected by distributing questionnaires and analyzed using a descriptive quantitative model; a five-point Likert Scale, a weighted mean score, a mean combined score, and a score interval to put the results based on their criteria. The result shows that the language attitude of the Acehnese parents is in good criterion (4.2); they honor, respect, and are proud of speaking the language as their identity. Moreover, they also put some genuine efforts into maintaining and inheriting the language by speaking the language while interacting with the spouse, children, and other Acehnese community members; and promoting the language to their children in several ways despite living in urban areas.